Discovering the teacher’s beliefs in TPACK framework for teaching English in high school - TAOPAN, LITA LIVIANI; DRAJATI, NUR ARIFAH; -, Sumardi (IJIE (Indonesian Journal of Informatics Education), 2019)
Teacher’ belief is essential in classroom practice because it is the principle that teachers hold to be true and the rationale of the attitude in the classroom. In applying the TPACK framework, the teacher has to believe in it. This study intended to reveal the story of an English teacher regarding her beliefs in the TPACK framework for teaching English in high school and reveal how these beliefs shaped during her teaching career. To collect the data, the researcher used a semi-structured interview, observations, and document analysis. The participant was an experienced English Teacher in a high school in Indonesia. A narrative inquiry with the thematic analysis was applied to analyze the interview data. The study revealed that the teacher holds several beliefs in the TPACK framework for teaching English. First, the TPACK framework will be a success when the technology, pedagogy, and content knowledge are well-balanced. Second, the teacher also believes that technology integration should facilitate students to learn English easier. The third, negotiation in classroom is important. These beliefs shaped through experiences, training, contextual factor, and classroom practice. The findings are beneficial input for English language teachers in the developing country dealing with the TPACK implementation in the classroom